2020
DOI: 10.1016/j.robot.2020.103451
|View full text |Cite
|
Sign up to set email alerts
|

I-Support: A robotic platform of an assistive bathing robot for the elderly population

Abstract: In this paper we present a prototype integrated robotic system, the I-Support bathing robot, that aims at supporting new aspects of assisted daily-living activities on a real-life scenario. The paper focuses on describing and evaluating key novel technological features of the system, with the emphasis on cognitive human-robot interaction modules and their evaluation through a series of clinical validation studies. The I-Support project on its whole has envisioned the development of an innovative, modular, ICTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 58 publications
1
41
0
1
Order By: Relevance
“…On the other hand, the plan created must be able to control the robot while performing both CGA tests and rehabilitation sessions in a similar way as the specific domains allowed. It is important to bear in mind that building specific models for each particular HRI task is the common approach found in the state-of-the-art [ 4 , 5 , 6 ], so the aim of the proposed evaluation is to check if that specific domains can be replaced by a single one keeping reaction times and making the robot to externally behave in the same way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the plan created must be able to control the robot while performing both CGA tests and rehabilitation sessions in a similar way as the specific domains allowed. It is important to bear in mind that building specific models for each particular HRI task is the common approach found in the state-of-the-art [ 4 , 5 , 6 ], so the aim of the proposed evaluation is to check if that specific domains can be replaced by a single one keeping reaction times and making the robot to externally behave in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…Social robots [ 1 ] must autonomously interact with people on dynamic and uncertain environments. A common way to control such robots is the use of finite-state machines (FSM) [ 2 , 3 , 4 , 5 , 6 ], where each state corresponds to a certain situation during the interaction, and transitions between states depend both on actions performed by the robot and information received by sensors. FSMs are simple and fast mechanisms to control the robot, particularly in structured environments, but, in more sophisticated applications, to identify and correctly specify all possible states that could appear and the transitions among them can be a really hard task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the integration of action recognition solutions in ARDs, different studies revealed that this capability is fundamental for the interactions with the users [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Most of the approaches need a set of sensors to be installed in the home of the user, e.g., [ 30 , 31 , 32 ].…”
Section: Related Workmentioning
confidence: 99%
“…Finally, some works offer a real-time action recognition capability using the cameras installed directly within the robotic platforms [ 35 , 36 , 37 , 38 ].…”
Section: Related Workmentioning
confidence: 99%